Landscape simplification shapes pathogen prevalence in plant‐pollinator networks. (28th April 2020) - Figueroa, Laura L.; Grab, Heather; Ng, Wee Hao; Myers, Christopher R.; Graystock, Peter; McFrederick, Quinn S.; McArt, Scott H.
Abstract: Species interaction networks, which play an important role in determining pathogen transmission and spread in ecological communities, can shift in response to agricultural landscape simplification. However, we know surprisingly little about how landscape simplification‐driven changes in network structure impact epidemiological patterns. Here, we combine mathematical modelling and data from eleven bipartite plant‐pollinator networks observed along a landscape simplification gradient to elucidate how changes in network structure shape disease dynamics. Our empirical data show that landscape simplification reduces pathogen prevalence in bee communities via increased diet breadth of the dominant species. Furthermore, our empirical data and theoretical model indicate that increased connectance reduces the likelihood of a disease outbreak and decreases variance in prevalence among bee species in the community, resulting in a dilution effect. Because infectious diseases are implicated in pollinator declines worldwide, a better understanding of how land use change impacts species interactions is therefore critical for conserving pollinator health. Abstract : We combined mathematical modeling and data from eleven plant‐pollinator networks observed along a landscape simplification gradient to elucidate how changes in network structure shape disease dynamics. Our empirical data show that landscape simplification reduces pathogen prevalence in bee communities via increased diet breadth of the dominant species. Furthermore, our empirical data and theoretical model indicate that increased connectance reduces the likelihood of a disease outbreak and decreases variance in prevalence among bee species in the community, resulting in a dilution effect.